Targeting the m6A RNA methyltransferase METTL3 attenuates the development of kidney fibrosis - Jung, Hae Rim; Lee, Jeonghwan; Hong, Seung-Pyo; Shin, Nayeon; Cho, Ara; Shin, Dong-Jin; Choi, Jin Woo; Kim, Jong-Il; Lee, Jung Pyo; Cho, Sung-Yup (Experimental & molecular medicine, 2024)
Kidney fibrosis is a major mechanism underlying chronic kidney disease (CKD). N 6 -methyladenosine (m 6 A) RNA methylation is associated with organ fibrosis. We investigated m 6 A profile alterations and the inhibitory effect of RNA methylation in kidney fibrosis in vitro (TGF-β-treated HK-2 cells) and in vivo (unilateral ureteral obstruction [UUO] mouse model). METTL3-mediated signaling was inhibited using siRNA in vitro or the METTL3-specific inhibitor STM2457 in vivo and in vitro. In HK-2 cells, METTL3 protein levels increased in a dose- and time-dependent manner along with an increase in the cellular m 6 A levels. In the UUO model, METTL3 expression and m 6 A levels were significantly increased. Transcriptomic and m 6 A profiling demonstrated that epithelial-to-mesenchymal transition- and inflammation-related pathways were significantly associated with RNA m 6 A methylation. Genetic and pharmacologic inhibition of METTL3 in HK-2 cells decreased TGF-β-induced fibrotic marker expression. STM2457-induced inhibition of METTL3 attenuated the degree of kidney fibrosis in vivo. Furthermore, METTL3 protein expression was significantly increased in the tissues of CKD patients with diabetic or IgA nephropathy. Therefore, targeting alterations in RNA methylation could be a potential therapeutic strategy for treating kidney fibrosis. RNA methylation: a new player in chronic kidney disease progression Kidney fibrosis, a significant element in chronic kidney disease, is connected to RNA methylation (a process that controls gene activity). In research by Jung Pyo Lee and Sung-Yup Cho, they examined changes in RNA methylation during kidney fibrosis and its possibility as a treatment target. The scientists used both in vitro (in a controlled environment like a test tube) and in vivo (within a living organism) models of kidney fibrosis, discovering that stopping METTL3, a crucial enzyme in RNA methylation, lessened kidney fibrosis. They also observed a considerable increase in METTL3 protein expression in the tissues of patients with chronic kidney disease, implying that focusing on changes in RNA methylation could be a potential strategy for treating kidney fibrosis. This study emphasizes the significance of RNA methylation in kidney fibrosis and its potential as a treatment target. This summary was initially drafted using artificial intelligence, then revised and fact-checked by the author.